The preposition "( Min من)" and its famous meanings in the Holy Quran: حرف الجر " من" ومعانيها الشهيرة في القرآن الكريم - Dr. Bashir Ahmad; Dr. Muhammad Ilyas (Al-Mahdi Research Journal (MRJ), 2024)
Arabic grammar is the grammar of the Arabic language which is a Semitic language. It also can be divided into two types Literary Arabic and Colloquial Arabic. Again, Literary Arabic is divided into Classical Arabic and Modern Standard Arabic. Arabic is not only a vital language but also required for people from around the world for various reasons. Arabic is having immense importance for scholars, educationists, linguists, artists, and business professionals. Learning Arabic grammar (Nahw) is essential to mastering the Arabic language. Therefore, non-native Arabic speakers need to practice and exert effort to learn Arabic grammar, as each grammatical rule will be a new rule for them. This research deals with the ‘huruf al-jarr’ (prepositions). From these Haroof “huruf al-jarr’ “( Min من) used in Arabic sentences. The research relied on the descriptive analytical approach in light of Different Tafaseers as it is appropriate for the study. The study’s main results reveal that the actual particle (al-Harf al-Asli) must produce a new meaning that did not exist before its addition to the sentence.